CORRELATION BETWEEN FREQUENCY AND DURATION ON READING THEQUR’AN WITH COGNITIVE FUNCTION AT ELDERLY - Soesilowati Tri Indrijaningrum, Pipit; Hamdan, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Background: The population of elderly people in Indonesia is increasing, so a decrease in cognitive function will be more common to be found; therefore, the implementation of cognitive activity of reading as a nonpharmacological management is needed to maximize cognitive function in the elderly. Objectives: To know the existence of a relation between frequency and duration of reading Al-Quran with cognitive function in the elderly. Methods: This study used a case-control and sampling design that was conducted according to incident cases. In the study, subjects performed cognitive function examinations with a MoCa-Ina questionnaire, then measured the frequency and duration of reading Al-Quran by interview. The data analysis was using Chi-square. Results: There were 68 study subjects, consisting of 34 subjects with abnormal cognitive function and 34 subjects with normal cognitive. Out of the 34 subjects who have cognitive abnormalities, there were 27 (50.9%) people who read the Quran with a frequency <12 x/week, and 7 (46.7%) people read with a frequency ≥12 x/week. There was no correlation between the frequency of reading the Quran and cognitive function (p = 0.770). Then, 34 subjects whose cognitive abnormalities were 14 (40%) people who read the Quran, with a duration of 1 times reading <30 minutes and 20 (60.6%) people who read the Quran, with a duration of 1 times reading ≥30 minutes. Conclusion: There was no correlation between the duration of reading the Quran and cognitive function (p = 0.0890) Conclusion: There was no correlation between the frequency and duration of reading the Quran and cognitive function in the elderly.